Organic Chemistry in the H2-bearing, CO-rich Interstellar Ice Layer at Temperatures Relevant to Dense Cloud Interiors - Rafael Martín-Doménech; Alexander DelFranco; Karin I. Öberg; Mahesh Rajappan (The Astrophysical Journal, 2024)
Ice chemistry in the dense, cold interstellar medium (ISM) is probably responsible for the formation of interstellar complex organic molecules (COMs). Recent laboratory experiments performed at T ∼ 4 K have shown that irradiation of CO:N _2 ice samples analog to the CO-rich interstellar ice layer can contribute to the formation of COMs when H _2 molecules are present. We have tested this organic chemistry under a broader range of conditions relevant to the interior of dense clouds by irradiating CO: ^15 N _2 :H _2 ice samples with 2 keV electrons in the 4–15 K temperature range. The H _2 ice abundance depended on both, the ice formation temperature and the thermal evolution of the samples. Formation of H-bearing organics such as formaldehyde (H _2 CO), ketene (C _2 H _2 O), and isocyanic acid (H ^15 NCO) was observed upon irradiation of ice samples formed at temperatures up to 10 K, and also in ices formed at 6 K and subsequently warmed up and irradiated at temperatures up to 15 K. These results suggest that a fraction of the H _2 molecules in dense cloud interiors might be entrapped in the CO-rich layer of interstellar ice mantles, and that energetic processing of this layer could entail an additional contribution to the formation of COMs in the coldest regions of the ISM.